GROWTH, YIELD AND QUALITY OF SUGARCANE (SACCHARUM SPP. HYBRID COMPLEX) AS INFLUENCED BY INTEGRATED NUTRIENT MANAGEMENT AND GENOTYPES - ANOOP KUMAR RATHORE; HARENDRA SINGH; RITUJA JAIN (The Bioscan, 2014)
A field investigation was carried out at Crop Research Centre, Rajendra Agricultural University, Pusa, Bihar during spring season of 2012-13 to evaluate the effect of integrated nutrient management and genotypes on growth, yield and quality of sugarcane. The results indicated that significant improvement of higher growth, yield attributes and yield in terms of tillers (149.53×103/ha), plant height (293.47 cm), millable canes (116.19×103/ ha), cane yield (93.90 t/ha) and sugar yield (10.82 t/ha) were recorded with application of 100% RDN through chemical fertilizer + 25% RDN through pressmud. Among three midlate genotypes, ‘BO 154’ resulted significantly highest tillers (161.43×103 /ha), plant height (292.57 cm), millable canes (124.04×103/ha), cane yield (94.68 t/ha) and sugar yield (11.04 t/ha).